THEO VAN LEEUWEN'S INCLUSION THEORY IN ECONOMIC NEWS THEME OF TRADING COMPASSES IN NOVEMBER 2018 - Sonya Patalia; Risma Anriani; Dede Abdurrakhman (JLER (Journal of Language Education Research), 2020)
This research aims to analyze usage Leeuwen Inclusion theory in economic news with the theme of trading in the November Kompas newspaper 2018. Three steps were taken in the collection of data namely, (1) understand and read discourse with the theme of investment in the November Kompas newspaper 2018, (2) the discourse will be marked on the parts which is related to inclusion theory, (3) Analyzing the data carried out descriptively. Based on the result of the study it can be concluded, in 3 economic news title with the theme of invetment in the Nove,ber Kompas newspaper 2018 found the Leeuwen inclusion theory. Of the seven theories that exist the author found five theories namely, indifferentation-differentation, objectivities-abstractoin, nomination- categorization, , determination-indetermination.